KEBEBASAN KEHENDAK DALAM AL-QUR’AN: STUDI TAFSIR MU’TAZILAH - Muhammad Rizky HK (el-'Umdah, 2021)
This article will describe the quranic interpretation of Mu’tazilite on theological verses which talked about free will. As a rationalist sect in Islamic tradition, Mu’tazilite offered different perspective, which has been known as a more logical sect than a mainstream thought in Islam. As a result, they came with a different perspective on a lot of theological aspects. Mu’tazilite believes, that human have a freedom to choose, Human has a free will. They are free to choose between good and evil. There’s no divine intervention in human act. In modern era, Existensialism came with same statement that human should be free. Existensialist believes that human existensce preceed their essence. This paper will describe the similarity of these two and would try to identificate mu’tazilite method of interpretation with existensialist point of view. This article use qualitative research method with descriptive analysis approach through the collection of related literature studies especially The thought of Jean Paul Sartre and Soren Kierkegaard, Two biggest existensialist. The results of this study indicate that the conception offree will has relevance with Islamic tradition itself, and have a relation wih western philosophy.